The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/mc.22924
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of reactive oxygen species (ROS) for the proapoptotic effects of indirubin derivative DKP‐073 in melanoma cells

Abstract: Melanoma represents a prime example demonstrating the success of targeted therapy in cancer. Nevertheless, it remained a deadly disease until now, and the identification of new, independent strategies as well as the understanding of their molecular mechanisms may help to finally overcome the high mortality. Both indirubins and TNF‐related apoptosis‐inducing ligand (TRAIL) represent promising candidates. Here, the indirubin derivative DKP‐073 is shown to trigger apoptosis in melanoma cells, which is enhanced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 51 publications
(115 reference statements)
0
23
0
Order By: Relevance
“…Thus, antioxidants prevented Thr-167 phosphorylation and partially rescued melanoma cells from wortmannin/TRAIL-induced apoptosis [59]. The significance of ROS for apoptosis regulation in melanoma cells was reported [100,101,102], and ROS was also involved in sensitization of melanoma cells for TRAIL by cell cycle inhibition [84]. Together, these data suggest that an early Bax activation is the critical step in sensitization of melanoma cells for TRAIL, which then allows release of Smac.…”
Section: Critical Contribution Of Mitochondrial Pathways and Bcl-2mentioning
confidence: 99%
“…Thus, antioxidants prevented Thr-167 phosphorylation and partially rescued melanoma cells from wortmannin/TRAIL-induced apoptosis [59]. The significance of ROS for apoptosis regulation in melanoma cells was reported [100,101,102], and ROS was also involved in sensitization of melanoma cells for TRAIL by cell cycle inhibition [84]. Together, these data suggest that an early Bax activation is the critical step in sensitization of melanoma cells for TRAIL, which then allows release of Smac.…”
Section: Critical Contribution Of Mitochondrial Pathways and Bcl-2mentioning
confidence: 99%
“…Recent studies showed that indirubin derivatives DKP-071 and DKP-073 can activate the apoptotic pathway in cutaneous T-cell lymphoma and melanoma cells by inducing the production of reactive oxygen species (ROS) (Soltan et al, 2019;Zhivkova et al, 2019). Oxidative stress and elevation of ROS induced by chemicals have pleiotropic deleterious effects including developmental toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…As concerning the pathways, by which indirubins may exert their effects, multiple targets have been suggested including CDKs, GSK-3β, pRb, c-Src, FGF-R1, VEGFR, STAT3, c-Jun and JNK2 [23,24,25,26]. In melanoma cells, we have previously shown that indurubin derivatives enhance extrinsic apoptosis pathways as induced by TRAIL (TNF-related apoptosis-inducing ligand [27,28]. Extrinsic apoptosis pathways via caspase-8/caspase-3 are of particular importance for apoptosis regulation in CTCL cells [10,34].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) play important roles in tissue damage and aging, and antioxidative strategies were established to prevent these negative effects. Besides this, ROS may also be involved in proapoptotic signaling in cancer cells [16,28,35,36]. As an example from the clinic, photodynamic therapy (PDT), used for the treatment of actinic keratosis, results in the production of high amounts of singlet oxygen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation